Development of a Web-Based Contractor Safety Management System (CSMS): A Case Study of PT. Petromine Energi Trading - Usman, Usman; Rokhmat, Nur (Universitas Bina Darma, 2025)
This study aimed to develop a Contractor Safety Management System (CSMS) to support the program implemented by PT. Petromine Energi Trading, aligning with the company’s objectives for managing the CSMS within the framework of the Mining Safety Management System (SMKP). The technical approach focused on creating a web-based application using a user-centered design (USD) methodology. The results showed that the integration of Single Sign-On (SSO) in the web-based platform enhanced user convenience by allowing seamless access and interaction with the CSMS. The backend structure of the system was designed to facilitate efficient data management and ensure secure, real-time information processing. The CSMS was also developed to ensure compliance with national regulations and international standards while improving communication and coordination between PT. Petromine Energi Trading and its contractors, supporting the comprehensive management of Occupational Health and Safety (OHS) risks.